Pterois volitans ... - Ditty, James G.; Malca, Estrella; Vásquez-Yeomans, Lourdes (Zenodo, 2024)
Pterois volitans: general morphology We measured nine P. volitans larvae from 2.5–12.9 mm (Fig. 2a–g) and examined others as supplemental material. Smallest preflexion larva characterized by precocious pectoral fins, deep base, elongate rays. Gut with single loop or “twist” (Fig. 2a), and terminates slightly beyond mid-body; hindgut becomes rugose in early postflexion larvae. Flexion larvae with tips of longest developing pectoral rays to or beyond posterior margin of dorsal-fin base; by early postflexion, these rays extend to about terminal margin of caudal peduncle (CP) or beyond, if unbroken. Flexion larvae with pronounced “hump” in snout dorsal profile created by elevation of rostral cartilage (i.e., ascending process of premaxilla). Head deep, angle of lower jaw pronounced; snout typically 10–15% shorter than OD; CP shortens, deepens as notochord flexes. Upper jaw terminates near mid-orbit; maxilla deepens near terminal margin, its maximum depth>55% OD. CP depth nearly equal to its length in ... : Published as part of Ditty, James G., Malca, Estrella & Vásquez-Yeomans, Lourdes, 2024, The lionfishes: Comparative development of Pterois volitans, Dendrochirus barberi, and D. hemprichi (Scorpaeniformes: Scorpaenidae: Pteroinae) and discrimination of their early life stages from non-pteroine scorpaenid genera in the Western North Atlantic, pp. 1-41 in Zootaxa 5446 (1) on pages 8-12, DOI: 10.11646/zootaxa.5446.1.1, http://zenodo.org/record/11084543 ...